Pengaruh Harga Internasional Batubara, Harga Internasional Minyak Bumi dan Gross Domestic Product Per Capita Terhadap Permintaan Ekspor Batubara Indonesia Ke Jepang Tahun 2000-2020 - Wahyu Ida Nurcahyaningsih, Tri; Rahayu, SE, Astuti; Drs. Purwiyanta, M.Si, Drs. Purwiyanta, M.Si (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Indonesia's non-oil and gas exports are one of the sectors that contribute significantly to Indonesia's trade balance. This study aims to analyze the effect of international coal prices, international oil prices, and Japan's Gross Domestic Product Per Capita on demand for Indonesian coal exports to Japan in 2000-2020. This research is quantitative in nature, the type of data used is 21 year secondary time series data sourced from the World Bank, BP Statistical Review of World Energy, Ministry of Energy and Mineral Resources and other related sources. The analytical method of this research uses Error Correction Model (ECM) using Eviews 9 software. The results of this study indicate that in the short term coal prices and international oil prices have no effect on demand for Indonesian coal exports to Japan in 2000-2020, while GDP Per Capita Japan has a positive effect on the demand for Indonesian coal exports to Japan in 2000-2020. In the long term, coal prices have no effect on demand for Indonesian coal exports to Japan in 2000-2020, while international prices for petroleum and Japan's GDP Per Capita have a positive effect on demand for Indonesian coal exports to Japan in 2000-2020